# Class 10 RD Sharma Solutions – Chapter 6 Trigonometric Identities – Exercise 6.1 | Set 1

Last Updated : 30 Apr, 2021

### Question 1. (1 â€“ cos2 A) cosec2 A = 1

Solution:

We have,

L.H.S. = (1 â€“ cos2 A) cosec2 A

By using the identity, sin2 A + cos2 A = 1, we get,

= (sin2 A) (cosec2 A)

= sin2 A Ã— (1/sin2 A)

= 1

= R.H.S.

Hence proved.

### Question 2. (1 + cot2 A) sin2 A = 1

Solution:

We have,

L.H.S. = (1 + cot2 A) sin2 A

By using the identity, cosec2 A = 1 + cot2 A, we get,

= cosec2 A sin2 A

= (1/sin2 A) Ã— sin2 A

= 1

= R.H.S

Hence proved.

### Question 3. tan2 Î¸ cos2 Î¸ = 1 âˆ’ cos2 Î¸

Solution:

We have,

L.H.S. = tan2 Î¸ cos2 Î¸

= (sin2 Î¸/cos2 Î¸) (cos2 Î¸)

= sin2 Î¸

= 1 âˆ’ cos2 Î¸

= R.H.S.

Hence proved.

### Question 4. cosec Î¸ âˆš(1 â€“ cos2 Î¸) = 1

Solution:

We have,

L.H.S. = cosec Î¸ âˆš(1 â€“ cos2 Î¸)

= cosec Î¸ âˆš(sin2 Î¸)

= cosec Î¸ sin Î¸

= (1/sin Î¸) (sin Î¸)

= 1

= R.H.S.

Hence proved.

### Question 5. (sec2 Î¸ âˆ’ 1)(cosec2 Î¸ âˆ’ 1) = 1

Solution:

We have,

L.H.S. = (sec2 Î¸ âˆ’ 1)(cosec2 Î¸ âˆ’ 1)

By using the identities sec2 Î¸ âˆ’ tan2 Î¸ = 1 and cosec2 Î¸ âˆ’ cot2 Î¸ = 1, we have,

= tan2 Î¸ cot2 Î¸

= (tan2 Î¸) (1/tan2 Î¸)

= 1

= R.H.S.

Hence proved.

### Question 6. tan Î¸ + 1/tan Î¸ = sec Î¸ cosec Î¸

Solution:

We have,

L.H.S. = tan Î¸ + 1/ tan Î¸

= (tan2 Î¸ + 1)/tan Î¸

= sec2 Î¸/tan Î¸

= 1/sin Î¸ cos Î¸

= sec Î¸ cosec Î¸

= R.H.S.

Hence proved.

### Question 7. cos Î¸/(1 â€“ sin Î¸) = (1 + sin Î¸)/cos Î¸

Solution:

We have,

L.H.S. = cos Î¸/(1 â€“ sin Î¸)

= (1 + sin Î¸)/cos Î¸

= R.H.S.

Hence proved.

### Question 8. cos Î¸/(1 + sin Î¸) = (1 â€“  sin Î¸)/cos Î¸

Solution:

We have,

L.H.S. = cos Î¸/(1 + sin Î¸)

= (1 â€“  sin Î¸)/cos Î¸

= R.H.S.

Hence proved.

### Question 9. cos2 Î¸ + 1/(1 + cot2 Î¸) = 1

Solution:

We have,

L.H.S. = cos2 Î¸ + 1/(1 + cot2 Î¸)

= cos2 Î¸ + 1/(cosec2 Î¸)

= cos2 Î¸ + sin2 Î¸

= 1

= R.H.S.

Hence proved.

### Question 10. sin2 A + 1/(1 + tan2 A) = 1

Solution:

We have,

L.H.S. = sin2 A + 1/(1 + tan2 A)

= sin2 A + 1/(sec2 A)

= sin2 A + cos2 A

= 1

= R.H.S.

Hence proved.

### Question 11.  = cosec Î¸ âˆ’ cot Î¸

Solution:

We have,

L.H.S. =

= cosec Î¸ âˆ’ cot Î¸

= R.H.S.

Hence proved.

### Question 12. (1 â€“ cos Î¸)/sin Î¸ = sin Î¸/(1 + cos Î¸)

Solution:

We have,

L.H.S. = (1 â€“ cos Î¸)/sin Î¸

= sin Î¸/(1 + cos Î¸)

= R.H.S.

Hence proved.

### Question 13. sin Î¸/(1 â€“ cos Î¸) = cosec Î¸ + cot Î¸

Solution:

We have,

L.H.S. = sin Î¸/(1 â€“ cos Î¸)

= cosec Î¸ + cot Î¸

= R.H.S.

Hence proved.

### Question 14. (1 â€“ sin Î¸)/(1 + sin Î¸) = (sec Î¸ â€“ tan Î¸)2

Solution:

We have,

L.H.S. = (1 â€“ sin Î¸)/(1 + sin Î¸)

= (sec Î¸ â€“ tan Î¸)2

= R.H.S.

Hence proved.

Solution:

We have,

L.H.S. =

= cos Î¸/sin Î¸

= cot Î¸

= R.H.S.

Hence proved.

### Question 16. tan2 Î¸ âˆ’ sin2 Î¸ = tan2 Î¸ sin2 Î¸

Solution:

We have,

L.H.S. = tan2 Î¸ âˆ’ sin2 Î¸

= sin2 Î¸/cos2 Î¸ âˆ’ sin2 Î¸

= sin2 Î¸(1/cos2 Î¸ âˆ’ 1)

= sin2Î¸ (sin2Î¸/cos2Î¸)

= tan2 Î¸ sin2 Î¸

= R.H.S.

Hence proved.

### Question 17. (cosec Î¸ + sin Î¸)(cosec Î¸ â€“ sin Î¸) = cot2Î¸ + cos2Î¸

Solution:

We have,

L.H.S. = (cosec Î¸ + sin Î¸)(cosec Î¸ â€“ sin Î¸)

= cosec2 Î¸ â€“ sin2 Î¸

= (1 + cot2 Î¸) â€“ (1 â€“ cos2 Î¸)

= 1 + cot2 Î¸ â€“ 1 + cos2 Î¸

= cot2 Î¸ + cos2 Î¸

= R.H.S.

Hence proved.

### Question 18. (sec Î¸ + cos Î¸) (sec Î¸ â€“ cos Î¸) = tan2 Î¸ + sin2 Î¸

Solution:

We have,

L.H.S. = (sec Î¸ + cos Î¸) (sec Î¸ â€“ cos Î¸)

= sec2 Î¸ â€“ cos2 Î¸

= (1 + tan2 Î¸) â€“ (1 â€“ sin2 Î¸)

= 1 + tan2 Î¸ â€“ 1 + sin2 Î¸

= tan2 Î¸ + sin2 Î¸

= R.H.S

Hence proved.

### Question 19.sec A(1 â€“ sin A) (sec A + tan A) = 1

Solution:

We have,

L.H.S. = sec A(1 â€“ sin A) (sec A + tan A)

= 1

= R.H.S

Hence proved.

### Question 20. (cosec A â€“ sin A)(sec A â€“ cos A)(tan A + cot A) = 1

Solution:

We have,

L.H.S. = (cosec A â€“ sin A)(sec A â€“ cos A)(tan A + cot A)

= 1

= R.H.S

Hence proved.

### Question 21. (1 + tan2 Î¸)(1 â€“ sin Î¸)(1 + sin Î¸) = 1

Solution:

We have,

L.H.S. = (1 + tan2 Î¸)(1 â€“ sin Î¸)(1 + sin Î¸)

= (sec2 Î¸) (1 â€“ sin2 Î¸)

= (sec2 Î¸) (cos2 Î¸)

= 1

= R.H.S

Hence proved.

### Question 22. sin2 A cot2 A + cos2 A tan2 A = 1

Solution:

We have,

L.H.S. = sin2 A cot2 A + cos2 A tan2 A

= sin2 A (cos2 A/sin2 A) + cos2 A (sin2 A/cos2 A)

= cos2 A + sin2 A

= 1

= R.H.S.

Hence proved.

### (i) cot Î¸ â€“ tan Î¸ =

Solution:

We have,

L.H.S. = cot Î¸ â€“ tan Î¸

= cos Î¸/sin Î¸ â€“ sin Î¸/cos Î¸

= R.H.S.

Hence proved.

### (ii) tan Î¸ â€“ cot Î¸=

Solution:

We have,

L.H.S. = tan Î¸ â€“ cot Î¸

= sin Î¸/cos Î¸ â€“ cos Î¸/sin Î¸

= R.H.S.

Hence proved.

### Question 24. (cos2 Î¸/sin Î¸) â€“ cosec Î¸ + sin Î¸ = 0

Solution:

We have,

L.H.S. = (cos2 Î¸/sin Î¸) â€“ cosec Î¸ + sin Î¸

= 0

= R.H.S.

Hence proved.

Solution:

We have,

L.H.S. =

= 2 sec2 A

= R.H.S.

Hence proved.

Solution:

We have,

L.H.S. =

= 2 sec Î¸

= R.H.S.

Hence proved.

Solution:

We have,

L.H.S. =

= R.H.S.

Hence proved.

### Question 28.

Solution:

We have,

L.H.S. =

= sec2 Î¸/cosec2 Î¸

= tan2 Î¸

= R.H.S.

Hence proved.

Previous
Next